2006
DOI: 10.1111/j.1742-7843.2006.pto_499.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lipoic Acid and Dihydrolipoic Acid on 4‐Aminophenol‐Mediated Erythrocytic Toxicity in vitro*

Abstract: The effects of the antioxidant lipoic acid and its reduced form, dihydrolipoic acid (DHLA), were studied on the process of the erythrocytic toxicity of 4-aminophenol in human erythrocytes in vitro. 4-Aminophenol alone caused a stepwise increase in methaemoglobin formation, along with a commensurate decrease in total thiols. At 10 min., in the presence of lipoic acid alone and the thiol depletor 1-chloro-2,4-dinitrobenzene (CDNB) alone, 4-aminophenol-mediated methaemoglobin formation was significantly increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…Therefore, it is important to determine which is the active compound, ALA or DHLA, to exert various beneficial effects. It is known that ALA and DHLA do not show equivalent efficacy in several physiological activities (Muller and Menzel 1990;Lapenna et al 2003;Coleman et al 2006). The present study was performed to elucidate the differences in the cytotoxic activities of ALA and DHLA.…”
Section: Introductionmentioning
confidence: 95%
“…Therefore, it is important to determine which is the active compound, ALA or DHLA, to exert various beneficial effects. It is known that ALA and DHLA do not show equivalent efficacy in several physiological activities (Muller and Menzel 1990;Lapenna et al 2003;Coleman et al 2006). The present study was performed to elucidate the differences in the cytotoxic activities of ALA and DHLA.…”
Section: Introductionmentioning
confidence: 95%
“…Dihydrolipoic acid inhibits tetrachlorohydroquinone‐induced tumor promotion via prevention of oxidative damage (Wang et al,2008). Conversely, other studies show that lipoic acid and DHLA induce apoptosis through promotion of intracellular oxidative stress (Wenzel et al2005; Coleman et al2006). In this study, we demonstrated that DHLA directly induces oxidative stress in ESC‐B5 cells (Fig.…”
Section: Discussionmentioning
confidence: 91%
“…Although lipoic acid has been extensively investigated clinically and has been shown to be effective, it is capable of acting as a pro‐oxidant in certain conditions [8,26]. Although the closed system explored in this report is unlike the cellular environment in normal human erythrocytes, it is possible to speculate that in certain circumstances such as hypoglycaemia, high doses of lipoic acid might lead to depletion of cellular thiols, which could promote oxidative stress and cellular toxicity.…”
Section: Discussionmentioning
confidence: 98%